The role of monetary and non-monetary shocks in children’s schooling in the presence of credit market imperfection in Cameroon - Olivier Ewondo Mbebi; Fabrice Nzepang; Romeal Eboue; Carlos Rigobert Ewane Nkoumba (International Journal of Social Economics, 2025)
Purpose This paper examines the determinants of children’s schooling under imperfect credit market conditions in Cameroon, with a particular focus on the role of monetary and non-monetary shocks. Design/methodology/approach The study uses microeconomic data from the fourth Cameroonian Household Survey (ECAM IV) conducted in 2014 by the National Institute of Statistics (INS) and an instrumental variable Probit model to demonstrate its point. Findings The results show that uncertainty about household income as measured by transitory income and declining household income decreases the probability of children attending school in Cameroon. The same is true for increasing household size. Nevertheless, access to the credit market is a factor in household resilience to shocks. Originality/value The purpose of this article is to contribute to the identification of the determinants of children’s schooling in Cameroon in a situation of credit market imperfection. The aim is to examine the influence of different household vulnerability factors and not only income shocks, which have long been considered the dominant factor. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/IJSE-01-2024-0028